Palavras que ocupam muito espaço – a resistência à ditadura militar na literatura infantil do Brasil e da Argentina (1970 – 1980) - Paula, Marcia Borges de Goes de (2023)
This paper looks at the role of children's literature in resisting the military dictatorship in Brazil (1964-1985) and Argentina (1976 - 1983) by studying the works História meio ao contrário (1977), by Ana Maria Machado, and the short story Un elefante ocupa mucho espacio (1975), by Elsa Bonermann. Like other cultural manifestations, children's literature suffered censorship and restrictions, being considered dangerous to "morals and good customs". The text highlights the importance of children's literature as a little-explored historical source that can help to understand the unknown past and identify social subjects and the world in which they lived. Historical research based on children's books can help to understand the ways in which authors expressed their ideas and feelings and, at the same time, exercised forms of political resistance in the context of dictatorial regimes.